O6 Ankle sprain history in a cohort of retired national football league athletes. (17th September 2017) - Kerr, ZY; Prim, J; DeFreese, JD; Thomas, LC; Wikstrom, EA
Abstract : Study Design: Cross-sectional survey. Objectives: To examine ankle sprain history in retired National Football League (NFL) athletes and their association with physical and mental health. Background: Ankle sprains are a common injury among athletes and are associated with long-term effects. Methods and Measures: In 2001 and 2010, 1233 former NFL athletes that had played between 1940–2000 s) completed General Health Surveys (GHS). In 2001, respondents recalled ankle sprains sustained during their NFL careers and whether these injuries currently affected health. Responses were used to create a three-category measure identifying those: (1) without ankle sprain history (n=993); (2) with ankle sprain history, but without current effects on health (n=130); and (3) with ankle sprain history and current effects on health (n=110). In 2010, respondents completed the VR-36, a validated health assessment yielding physical and mental component summary scores (PCS and MCS, respectively); higher scores indicated better health. Multiple linear regression estimated mean differences for PCS and MCS among the ankle sprain history groups; covariates included age, position played, race/ethnicity, and years played. Differences with 95% confidence intervals (CI) excluding 0.0 were significant. Results: Overall, 19.5% (n=240) reported ankle sprain histories during their NFL careers; 110 (45.8% of those with history) noted current effects on health. Mean PCS and MCS were 43.7±10.8 and 50.9±10.9, respectively. Controlling for covariates, mean PCS and MCS were lower in the 'history and affected group' than the 'no history' group (PCS difference=2.8; 95% CI:0.7–4.9; MCS difference=2.6; 95% CI:0.5–4.8) and 'history but not affected' group (PCS difference=3.6; 95% CI:0.9–6.3; MCS difference=2.9; 95% CI:0.1–5.6); no differences were found between the 'no history' and 'history but not affected' groups. Conclusions: Future research needs to identify how previously-sustained ankle sprains affect current health in former professional athlete populations. Our findings may highlight the benefits of proper management and care of injuries to mitigate long-term adverse effects.